PENGARUH MOTIVATION, ORGANIZATIONAL COMMITMENT DAN COMPETENCE REWARD TERHADAP PERFORMANCE - Cahyono, Krido Eko (Makro Jurnal Manajemen Dan Kewirausahaan, 2024)
The aim of this research is to examine the influence of motivation, organizational commitment and competency provision on teacher performance at SMA Muhammadiyah 1 Surabaya. The population used was all teachers at SMA Muhammadiyah 1 Surabaya. The sampling process used saturated sampling, namely sampling using all teachers of SMA Muhammadiyah 1 Surabaya. Based on the saturated sampling method, 37 respondents were obtained. Data collection uses a questionnaire. The research method used is a quantitative research method. The research analysis used in this research is multiple linear regression analysis with the SPSS version 26 application program. The results of the research show that the Motivation variable has a significant effect on Teacher Performance at SMA Muhammadiyah 1 Surabaya, the Organizational Commitment variable has a significant effect on Teacher Performance at SMA Muhammadiyah 1 Surabaya and the Giving variable. Competency has a significant effect on Teacher Performance at SMA Muhammadiyah 1 Surabaya.